Majālis-i Jahāngīrī : Majlishā-yi shabāna-yi darbār-i Nūr al-Dīn Jahāngīr - Lāhūrī, ʿAbd al-Sattār b. Qāsim, (Miras Maktoob, ISBN: 9789004365452., 2019)
Nūr al-Dīn Jahāngīr (d. 1037/1627) was the fourth Mughal emperor, son of emperor Akbar I (d. 1014/1605) and great-grandson of the founder of the Mughal dynasty, the Timurid prince Ẓahīr al-Dīn Muḥammad Bābur (d. 937/1530). Highly cultivated and a patron of the arts, especially portrait painting, Jahāngīr entertained many artists, literati and other members of the social and cultural elite at his court, where Persian was the dominant language. The author of the present work, ʿAbd al-Sattār b. Qāsim Lāhūrī, was a regular guest for a number of years. A specialist on foreign religions, especially Christianity, he was also present at many of the interreligious debates that were held in Jahāngīr's presence. Jahāngīr had such confidence in ʿAbd al-Sattār that he not only let him keep a record of his nightly entertainments published here, but also consulted him on what and what not to include in his personal record of his reign, the Jahāngīr-nāma.